2012
DOI: 10.1073/pnas.1201343109
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution between invasive and native plants driven by chemical competition and soil biota

Abstract: Although reciprocal evolutionary responses between interacting species are a driving force behind the diversity of life, pairwise coevolution between plant competitors has received less attention than other species interactions and has been considered relatively less important in explaining ecological patterns. However, the success of species transported across biogeographic boundaries suggests a stronger role for evolutionary relationships in shaping plant interactions. Alliaria petiolata is a Eurasian specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
144
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(156 citation statements)
references
References 52 publications
(65 reference statements)
5
144
2
2
Order By: Relevance
“…However, it has been shown that concentrations of these chemicals can evolve in response to the density of non-A. petiolata plants in the community (Lankau 2012) and will vary predictably based on the age of a particular A. petiolata population (Lankau et al 2009). Our estimate was in line with previous measures of sinigin in nearby Michigan populations, which found an average of 43.78 lmol/g in A. petiolata populations ranging from 21 to 67 years in age (R. Lankau, personal communication).…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been shown that concentrations of these chemicals can evolve in response to the density of non-A. petiolata plants in the community (Lankau 2012) and will vary predictably based on the age of a particular A. petiolata population (Lankau et al 2009). Our estimate was in line with previous measures of sinigin in nearby Michigan populations, which found an average of 43.78 lmol/g in A. petiolata populations ranging from 21 to 67 years in age (R. Lankau, personal communication).…”
Section: Discussionmentioning
confidence: 98%
“…). Furthermore, there is evidence that some native species have adapted to A. petiolata presence and chemistry including microbial communities (Lankau ), many native plants (Lankau , ; Lankau & Nodurft ) and the butterfly Pieris oleracea (Morton et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these past studies focus on contrasting performance between one species that occurs with (sympatric) or without (allopatric) one other species in common transplanted environments. Character displacement resulting from asymmetric competition is the most frequently suggested mechanism of biotic adaptation (Martin and Harding , Vavrek , Proffitt et al , Fridley et al , Lankau ). Our experimental design builds on the sympatric/allopatric treatment used in prior studies but is unique in contrasting communities of three co‐occurring woody species in sympatry and allopatry.…”
Section: Discussionmentioning
confidence: 99%